Pembelajaran Al-Qur’an dengan Metode Ijmaly Untuk Anak Usia Dini - Nurhayati, Eti (Program Studi Pendidikan Islam Anak Usia Dini, Fakultas Ilmu Tarbiyah dan Keguruan, UIN Sunan Kalijaga Yogyakarta, 2017)
There are many methods of learning the Qur'an for an early childhood that has been known andimplemented in society, among other methods: Baghdady, Lamma, Barqy, Iqra, Uktub, Qira'aty,Tilawaty, Integrated Iqra, Classical Iqra, Dirosah, and others. This paper intends to offer themethod